Learning, unlearning, and relearning from the past: Reassessing socialist modernist collective housing for sustainable urban regeneration in Sarajevo - Aida Idrizbegović Zgonić; Nermina Zagora; Mladen Burazor; Senka Ibrišimbegović (Urbani Izziv)

(untitled)
This article addresses a sustainable approach to urban regeneration in post-communist residential neighbourhoods in Sarajevo. The area explored is located in the municipality of Novo Sarajevo (literally, New Sarajevo), featuring well-known but somewhat controversial apartment buildings built after the Second World War, from the 1950s to the 1970s. At the time, this area epitomized the social and economic progress and expansion of the city from east to west, and it expressed the ideals of socialist modernist urban planning and architecture. More than seventy years later, following social, economic, and cultural transition after the war in the 1990s and new urban developments, this area and the city face multiple challenges, from decay to social bias. One key challenge is to adapt the residential architecture from socialist modernism to meet contemporary requirements of functionality and sustainability. This research proposes the “new urban protocol” as a collaborative model combining tools and procedures for sustainable urban regeneration while focusing on reevaluating, retrofitting, and reprograming the architectural legacy of socialist modernism.